Equine sarcoid events in equides - Nursal Metin; Harun Özer; M. Kemal Çiftçi (Eurasian Journal of Veterinary Sciences)
In equides 13 cases of equine sarcoides were investigated macrospically and microspically. These cases were obtained from one horse, tree mules and nine donkeys.